A meta-recovery framework: positioning the ‘New Recovery’ movement and other recovery approaches - Winship, Gary (Wiley, 2016)
This paper argues for a delineated explanation of the range of recovery approaches currently informing mental health interventions today. Four organizing domains of recovery are proposed: (1) Traditional Recovery; (2) Addictions Recovery; (3) New Recovery; and (4) Mutual Recovery. One of the challenges of providing mental health services efficiently is to consider which method of recovery is most suited to the needs of different service users. By comparing and organizing different recovery modalities, it is possible to consider the best fit between client and modality. For example, there is a necessary demarcation between clients who are amenable to recovery, and those who are harder to engage. We need to think about recovery in terms of the difference between ‘tender’ and ‘tough’ recovery approaches. A meta-recovery framework is proposed here as a basis for continuing discussions about the different types of recovery operational in the field of mental health today.